Robust Optimization of the Equity Momentum Strategy - Arco van Oord; Martin Martens; Herman K. van Dijk (Tinbergen Institute, 2009)
Quadratic optimization for asset portfolios often leads to error maximization, with optimizers zooming in on large errors in the predicted inputs, that is, expected returns and risks. The consequence in most cases is a poor real-time performance. In this paper we show how to improve real-time performance of the popular equity momentum strategy with robust optimization in an empirical application involving 1500-2500 US stocks over the period 1963-2006. We also show that popular procedures like Bayes-Stein estimated expected returns, shrinking the covariance matrix and adding weight constraints fail in such a practical case.
Keywords: G11; 330; quadratic optimization; momentum strategy; robust optimization; Portfolio-Management; Nichtlineare Optimierung; Anlageverhalten; Schätzung; USA